OPTIMALISASI PERAN FORUM ANAK DALAM MENSOSIALISASIKAN KEBIJAKAN KOTA LAYAK ANAK DI KOTA PALEMBANG - Miftahul Jannah; Amaliatulwalidain Amaliatulwalidain; Muhammad Quranul Kariem (Governance, 2022)
Children's Forum is a place of participation for children in the process of decision-making involvement in everything related to fighting for their rights consciously, understand and have a common will so that the child can enjoy the benefits of the results of his decision. The children's Forum has a leading role as a pioneer and Rapporteur. The method used in this study is qualitative. The results showed that the role of the Palembang City Children's Forum in socializing feasible city policies has not been optimal. And the purpose of this study is to optimize the role of the Palembang City Children's Forum as well as knowing the factors that become obstacles in socializing the Child-Friendly City Policy. The lack of optimization can be seen in the role of pioneers as agents of change who have not succeeded in getting people involved in making changes for the better for children while the role of reporters is only half of the fulfillment of children's rights that have just been reported. So in this case, advice is needed to increase the role of the child's Forum.